Host conservation through their parasites: molecular surveillance of vector-borne microorganisms in bats using ectoparasitic bat flies - Szentiványi Tamara; Markotter Wanda; Dietrich Muriel; Clément Laura; Ançay Laurie; Brun Loïc; Genzoni Eléonore; Kearney Teresa; Seamark Ernest; Estók Peter; Christe Philippe; Glaizot Olivier (Parasite, 2020)
Most vertebrates host a wide variety of haematophagous parasites, which may play an important role in the transmission of vector-borne microorganisms to hosts. Surveillance is usually performed by collecting blood and/or tissue samples from vertebrate hosts. There are multiple methods to obtain samples, which can be stored for decades if properly kept. However, blood sampling is considered an invasive method and may possibly be harmful to the sampled individual. In this study, we investigated the use of ectoparasites as a tool to acquire molecular information about the presence and diversity of infectious microorganism in host populations. We tested the presence of three distinct vector-borne microorganisms in both bat blood and bat flies: Bartonella bacteria, malaria-like Polychromophilus sp. (Apicomplexa), and Trypanosoma sp. (Kinetoplastea). We detected the presence of these microorganisms both in bats and in their bat flies, with the exception of Trypanosoma sp. in South African bat flies. Additionally, we found Bartonella sp. in bat flies from one population in Spain, suggesting its presence in the host population even if not detected in bats. Bartonella and Polychromophilus infection showed the highest prevalence in both bat and bat fly populations. Single, co- and triple infections were also frequently present in both. We highlight the use of haematophagous ectoparasites to study the presence of infectious microorganism in host blood and its use as an alternative, less invasive sampling method.